Brownies From Mangrove Fruit Flour: The Use of Variation of Flours as An Alternative to High Food Nutrition - Sumartini Sumartini; Kurnia Sada Harahap; Apri Mujiyanti (Indonesian Food and Nutrition Progress, 2020)
Brownies is a popular high-calorie snack.  In this studied, brownies were processed from several types of flour, namely pedada fruit (Sonneratia caseolaris) flour, api-api (Avicennia officinalis) flour, red bean flour, and modified cassava flour with nutritional value and health benefits compared to the commercial ones (from wheat flour).  The purpose of this studied was to determine the used of a variety of superior flours as raw material for making brownies in terms of nutritional value and leveled of preference.  The experimental design used a completely randomized design (CRD) with test parameters including the leveled of preference, caloric value, fiber, and proximate composition.  The results of the studied were tested for variance using spss version 22 software with a 95% confidence interval.  The results showed that the best results were brownies made from pedada fruit flour because they had higher fiber and lowered calories with test scores for calorie content, crude fiber, air content, fat content, protein content, ash content, carbohydrate content respectively.  401. 87 kcal each; 16.49%; 18.32%; 21.7%; 4.03%; 1.44%; and 54.64%.